Lattice microstructure design for cathode electrodes for high-performance lithium-ion batteries - Miranda, D. (2023)
The electrode geometry is an essential parameter affecting the cycling performance of batteries. In this work, the effect of lattice geometry of the cathode electrode on battery performance was studied by theoretical simulations keeping its volume constant. It was observed that the variation of the lattice geometry improves the cycling performance when compared to conventional planar geometry. The improvement of thr cycling performance in the lattice geometry is related to variations in the electrolyte current density. It was demonstrated that the lattice geometry allows to improve the discharge performance in lithium-ion batteries at higher discharge rates.